Prediksi Kepuasan Mahasiswa dengan Menggunakan Algoritma C4.5 terhadap Pelayanan Akademik - Rufiyanto, Anief; Rochcham, Muhammad; Rohman, Abdul (Jurusan Teknologi Informasi Universitas Semarang, 2021)
Prediction of student satisfaction with academic services needs to be done to evaluate the performance of higher education institutions in the academic field, especially at Pandanaran University. In this study, using the Decision Tree C4.5 algorithm data mining method in classifying student data through a questionnaire on aspects of tangible, reliability, assurance, responsiveness and empathy. The results of classifying student data using the Decision Tree C4.5 algorithm produce a decision tree model with an accuracy value of 87.92% and AUC 0.990.